Tunica Vaginalis Pedicle Flap Substitution Urethroplasty for Reconstruction of Anterior Urethral Stricture (KYAMC Journal, 2023)
Background: In long-segment urethral stricture, substitutional urethroplasty is the best option to get long-term good results. Though buccal mucosa is the most widely used tissue, it has limitations in some oral pathology. In several publications, there is evidence that Tunica vaginalis can be used as a graft or flap to reconstruct fibrotic urethra as well as to provide a vascularized covering to prevent subsequent urethrocutaneous fistula formation. This study evaluated the efficacy of the tunica vaginalis pedicle flap’s efficacy for managing anterior urethral stricture.Objectives: To evaluate the clinical efficacy of tunica vaginalis pedicle flap for reconstruction of anterior urethral stricture by assessing change in the maximum flow rate (Qmax), International prostatic symptom index (IPSS), postvoid residual urine (PVR) from baseline and the complication of surgery.Materials and Methods: This was a prospective clinical trial conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2017 to June 2018. A total of 15 patients were selected from the study population according to inclusion and exclusion criteria. The standard operation technique of urethroplasty by tunica vaginalis flap was followed. Patients were followed up after 3 months & 6 months to evaluate IPPS score, Qmax, flow time, PVR, and complications.Results: The mean age and stricture length of study participants were 38.93±11.38 years and 3.55±1.05 cm. The maximum flow of urine was 15.844±3.80 ml/sec at the final follow up which showed statistically significant improvement from baseline. There was also a significant improvement in IPSS, and quality of life during follow-up. Flow time and post-void residue reduced significantly from preoperative measurement. A total of 4 patients developed complications after the substitution of urethroplasty with tunica vaginalis.Conclusion: Tunica vaginalis pedicle flap may be an effective choice in the reconstruction of anterior urethral stricture.KYAMC Journal Vol. 14, No. 02, July 2023: 79-82.